2021
DOI: 10.2174/1871526520666200219110430
|View full text |Cite
|
Sign up to set email alerts
|

PCR Detection and Sequencing of Trichomonas vaginalis in Women with Suspected Vaginitis in Southwestern Iran

Abstract: Introduction: The human being is considered a natural host for Trichomonas vaginalis (T. vaginalis), which causes trichomoniasis, the most frequent non-viral sexually transmitted infectious disease in the world. The current study aimed to evaluate the prevalence and sequencing of T. vaginalis in women with vaginitis. Methods: In the current research, 514 vaginal discharge samples were obtained from women with vaginitis. The specimens were evaluated by the direct wet mount examination, Dorset culture medium,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Their results showed that the highest prevalence in women aged 31 to 40 years may be related to high sexual activity. In another study in southwest Iran, the prevalence of T. vaginalis was reported 5.83%, 8.75%, and 17.5% by using wet, culture medium, and PCR techniques, respectively [15]. The higher prevalence of infection in the other studies compared to our results could be due to the target populations, in the two above studies, the women with vaginitis and high-risk behaviors were exanimated, while the current study, evaluated trichomoniasis in women who attended regular health check-ups.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Their results showed that the highest prevalence in women aged 31 to 40 years may be related to high sexual activity. In another study in southwest Iran, the prevalence of T. vaginalis was reported 5.83%, 8.75%, and 17.5% by using wet, culture medium, and PCR techniques, respectively [15]. The higher prevalence of infection in the other studies compared to our results could be due to the target populations, in the two above studies, the women with vaginitis and high-risk behaviors were exanimated, while the current study, evaluated trichomoniasis in women who attended regular health check-ups.…”
Section: Discussionmentioning
confidence: 96%
“…However, the method is ineffective in diagnosing T. vaginalis in asymptomatic women due to its low sensitivity and specificity [13,14]. Studies have shown that molecular techniques such as polymerase chain reaction (PCR) have been widely employed for the specific detection of T. vaginalis [15]. However, limited information is available concerning PCR-based direct detection of T. vaginalis infections using liquid-based Pap samples.…”
Section: Introductionmentioning
confidence: 99%